Application of Artificial Intelligence in Libraries: Benefits and Drawbacks - Hasan, Nabi; Saifullah, Mohammad; Hashmi, Aashkar Hussain (Journal of Data Science, Informetrics, and Citation Studies)
Artificial Intelligence is revolutionising the different areas of life and libraries and information centres are no exceptions. Many libraries are now looking for new ways to improve their services, enhance library activities and meet the changing needs of their patrons. Artificial Intelligence or Machine Learning can help achieve these objectives. This article talks about Artificial Intelligence and its major components and presents a review of literature trying to determine what is happening in this domain. It further discusses AI applications in different areas of library information services, especially cataloguing, acquisition, reference services, circulation, indexing, robotics, etc. It further compares the benefits Vs drawbacks, as nothing comes without limitations or challenges. This basic exploration of AI applications in libraries could benefit a beginner or someone who has just started exploring the same.
Keywords: AI in libraries; Machine learning; Large Language Models; Robotics in libraries; Natural language processing; Expert systems; Automation in library operations; Human Intelligence.